Informing patients about drugs : analysis of alternative designs for estrogen leaflets - Kanouse, David E.; Berry, Sandra H., 1949-; Hayes-Roth, Barbara; Rogers, William H., 1951-; Winkler, John D., 1953-; Garfinkle, Jeffrey B. (Jeffrey Bruce), 1955-; Rand Corporation; United States. Food and Drug Administration (Santa Monica, CA : RAND, 1981)
The research reported is the most thorough investigation to date on the effects of patient package inserts (PPIs). It represents a prospective study of the effects of various prototype PPIs on actual drug users. Drug information documents can vary radically in format, length, content, and style. To determine what type of document works best, it is desirable to conduct experiments that systematically vary such factors as the content, style, and format of the document while controlling for other factors. The research in this report applies such a strategy to study alternative leaflets for conjugated estrogens, synthetic female hormones used primarily to treat vasomotor symptoms during menopause or following surgical removal of the ovaries. The results of three studies for this drug are presented, investigating the effects of six structural variables: specificity of instructions, amount of explanation, writing style, risk emphasis, format, and reduced content (length).
"August 1981."
Includes bibliographical references (p. 133-138).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Drugs -- Labeling; Estrogen; Pharmacy -- Information services -- Evaluation